Thinking, Pairing, and Sharing in the Classroom – A Pathway to Enhancing Students’ Contributions and Academic Achievement in Mathematics - Alabi, Ibraheem A.; Sanni, Rasheed; Oladejo, Adekunle I.; Sojinu, Sehubo Olawale; Akudo, Kennedy O.; Saibu, Sakibu Olajide (Journal of Educational Sciences, 2025)
Students' contributions had severely gone unnoticed in most mathematics classrooms as evident in their academic achievement which informed the conduct of this study. The study employed a mixed method design. The population was drawn from all Lagos State public senior secondary schools Two (grade 11) with samples consisting of 114 students (60 treatment group and 54 control group) conveniently selected from two schools. Face and content validity were used to validate the Mathematics Achievement Test. A reliability coefficient of 0.85 was obtained for quantitative aspect using the Kuder-Richardson formula 21 method while the qualitative aspect involved consensus coding of inter-rater reliability. For quantitative data, the research design was quasi-experimental while qualitative data was a case study. The results showed that students in Think-Pair-Share classes contribute more significantly to class activities than those in the control group. There is a significant difference between the academic achievement of students in a think-pair-share mathematics classroom and those in a conventional classroom [F (1,113) =39.69; p<0.05] in favour of the think-pair-share group. it was concluded that the quality of students’ contributions is directly proportional to academic achievement in mathematics classrooms.